Strategi Pengembangan Wisata Candi Umbul Kecamatan Grabag Kabupaten Magelang - Fitrah Sari Islami; Rr Retno Sugiharti; Jalu Aji Prakoso (Journal of Economics and Business, 2020)
The development of a tourist attraction requires an appropriate and applicable strategy, it cannot be compared to other attractions. This study aims to explore what strategies can be used in the development of the Umbul Temple Tourism Object located in Grabag District, Magelang Regency. Primary data were collected through interviews with visitors to the Umbul Temple tourist attraction. The method of analysis is done by using descriptive methods to be able to explain the priorities of policies and strategies in developing tourism objects. The results of the analysis state that there is still a need for development by changing the bottom-up pattern and the main priority in development in terms of facilities and infrastructure, culture, evaluation and institutional.